OPTIMALISASI BAHAN PEMBELAJARAN IPS BERBASIS TEKNOLOGI INFORMASI DI MGMP IPS JAKARTA TIMUR - Budiaman; Rusmono; Nandi Kurniawan (Bahasa Indonesia, 2019)
Abstract This community service program is aimed at empowering teachers to optimize information technology-based social studies learning materials. The partner in this community service activity is the MGMP IPS East Jakarta. The problem faced by partners is the gap in understanding of knowledge about syllabus development, learning materials, and learning media that can be optimized with current developments in information technology. The solution to overcome the problem is by providing assistance from formulating the problem, material orientation, group discussion, and assisting in the preparation of information technology-based social studies material. The method of implementing the activity was begun with a focus group discussion (FGD) between the Chairperson and the Executive Board of the East Jakarta MGMP. The results of the FGDs were implemented in the form of training and mentoring for social studies teachers with material: (1) syllabus development, (2) development of 21st century lesson plans, and (3) information technology-based learning media. The result of this activity was the increase in participants' knowledge and skills in compiling social studies learning materials. The product of the activities in the form of information technology-based learning materials in the form of lesson plans. In addition, workshop participants felt challenged to make information technology-based learning materials more diverse by continuing to realize the idealism of their profession Abstrak Kegiatan pengabdian kepada masyarakat terintegrasi KKN ini bertujuan untuk memberdayakan guru-guru dalam mengoptimalisasikan bahan pembelajaran IPS berbasis teknologi informasi. Mitra dalam kegiatan pengabdian kepada masyarakat ini adalah MGMP IPS Jakarta Timur. Permasalahan yang dihadapi mitra adalah adanya kesenjangan pemahaman pengetahuan tentang pengembangan silabus, bahan pembelajaran, dan media pembelajaran yang dapat dioptimalkan dengan perkembangan teknologi informas saat ini. Solusi untuk mengatasi permasalahan dengan melakukan pendampingan dari merumuskan masalah, orientasi materi, diskusi kelompok, dan pendampingan penyusunan materi IPS berbasis teknologi informasi. Metode pelaksanaan kegiatan dilakukan diawali dengan focus group discussion (FGD) antara Ketua Pelaksana dengan Pengurus MGMP Jakarta Timur. Hasil FGD diimplementasikan dalam bentuk pelatihan dan pendampingan guru-guru IPS dengan materi: (1) pengembangan silabus, (2) pengembangan RPP abad 21, dan (3) media pembelajaran berbasis teknologi informasi. Hasil kegiatan ini adalah meningkatnya pengetahuan peserta dan keterampilan dalam menysusun bahan pembelajaran IPS. Produk hasil kegiatan berupa bahan pembelajaran berbasis teknologi informasi dalam bentuk RPP. Selain itu peserta workshop merasa tertantang untuk membuat bahan pembelajaran berbasis teknologi informasi yang lebih beragam dengan terus mewujudkan idealisme profesinya secara konsisten.